Optimizing Art Skills in Students Through Creative Learning at UPTD SD Inpres Ngoramawo, Nusa Tenggara Timur, Indonesia - Ngoe, Hermanus Mardyan Trimulya; Fikri, Kanzul (Electronic Journal of Education, Social Economics and Technology, 2024)
This study aims to enhance students' musical arts skills through creative music learning using recycled percussion instruments. Art education in Indonesia often receives less attention despite its numerous benefits, making this research significant. The study adopts a descriptive qualitative approach, with data collected through observation, interviews, and document analysis conducted at SDI Ngoramawo, Bajawa District, Ngada Regency, as part of the Kampus Mengajar program. The collected data were analyzed qualitatively to identify patterns and themes related to the implementation of music learning and its impact on students' skills. The findings reveal that creative music learning with recycled percussion instruments enhances students' creativity, motor coordination, and social interaction skills. However, challenges such as limited resources and students' difficulties in grasping musical concepts were identified. The discussion highlights the importance of creating an engaging learning environment to foster students' interest in musical arts. This study concludes that the creative music learning approach is effective and beneficial, although efforts are needed to address existing challenges. It recommends that educators develop teaching strategies tailored to students' characteristics and incorporate environmental awareness into music learning. These findings are expected to inspire further development of music arts education in other schools.